2017
DOI: 10.3390/molecules22101646
|View full text |Cite
|
Sign up to set email alerts
|

Melandrii Herba Extract Attenuates H2O2-Induced Neurotoxicity in Human Neuroblastoma SH-SY5Y Cells and Scopolamine-Induced Memory Impairment in Mice

Abstract: Oxidative stress plays a significant role in the etiology of a variety of neurodegenerative diseases. In this study, we found that Melandrii Herba extract (ME) attenuated oxidative-induced damage in cells. Mechanistically, ME exhibited protection from H2O2-induced neurotoxicity via caspase-3 inactivation, Bcl-2 downregulation, Bax upregulation, and MAPK activation (ERK 1/2, JNK 1/2, and p38 MAPK) in vitro. Moreover, our in vivo data showed that ME was able to attenuate scopolamine-induced cognitive impairment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
(73 reference statements)
3
6
0
Order By: Relevance
“…H 2 O 2 -mediated ROS in SH-SY5Y cells can produce neurotoxicity by activating the MAPK cascade as shown in previous studies [ 24 26 ]. The results showed that phosphorylated proteins in the MAPK cascade (ERK1/2, JNK, P38) were significantly increased in the TI-induced gerbil’s hippocampus (Fig.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…H 2 O 2 -mediated ROS in SH-SY5Y cells can produce neurotoxicity by activating the MAPK cascade as shown in previous studies [ 24 26 ]. The results showed that phosphorylated proteins in the MAPK cascade (ERK1/2, JNK, P38) were significantly increased in the TI-induced gerbil’s hippocampus (Fig.…”
Section: Resultssupporting
confidence: 53%
“…The MAPK cascade signaling pathway can be activated during inflammation induced by cell and tissue injury [ 43 ]. In particular, oxidative stress caused by ROS generation plays a key role in activating the MAPK pathway which can be estimated by the phosphorylated ERK, JNK, and p38 kinase levels [ 44 ]. ERK plays a major role in regulating cell apoptosis by releasing cytochrome c and/or caspase-8 activation [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that H 2 O 2 -induced oxidative stress may cause neurotoxicity by activating the MAPK family [32][33][34]. As shown in Figure 7b, the phosphorylation of MAPK family proteins was dramatically elevated in SH-SY5Y cells after were challenged with H 2 O 2 alone.…”
Section: And Fcc Suppressed Mapk Signaling Pathways In Cellsmentioning
confidence: 68%
“…Oxidative stress initiated by ROS production and inflammation-induced cell and tissue injuries are important factors in the activation of the MAPK cascade [ 71 ]. Activation of the MAPK cascade can be predicted based on ERK, JNK, and p38 kinase activation [ 72 ]. When the MAPK cascade is activated, it triggers apoptosis by DNA damage or caspase-8 activation [ 14 , 73 ].…”
Section: Discussionmentioning
confidence: 99%